Developmental roles of Drosophila tRNA processing endonuclease RNase Z(L) as revealed with a conditional rescue system. - Xie, X.; Dubrovskaya, V.; Yacoub, N.; Walska, J.; Gleason, T.; Reid, K.; Dubrovsky, E.B. (Developmental Biology, 2013)
Drosophila RNase Z(L) (dRNaseZ) belongs to a family of endoribonucleases with a major role in tRNA 3'-end processing. The biochemical function of RNase Z(L) is conserved from yeast to human. Here we present a study of its biological function during Drosophila development. In flies, dRNaseZ provides a non-redundant function, as the RNZ(ED24) knockout (KO) mutation causes early larval lethality. Mosaic and conditional rescue techniques were employed to determine dRNaseZ requirements at later stages. We found that dRNaseZ activity is essential for all phases of fly development that involve cell division, including growth of adult tissue progenitors during larval and metamorphic stages, and gametogenesis in adults. At the cellular level, two major phenotypes were identified-cell growth deficiency in endoreplicating tissues and cell cycle arrest in mitotic tissues. While cell growth and proliferation are both dependant on protein synthesis, the two phenotypes displayed reliance on different dRNaseZ functions. We found that dRNaseZ KO completely blocks tRNA maturation without diminishing the abundance of mature tRNA molecules. Our data indicate that growth arrest of endoreplicating cells is primarily attributed to the relocation of the pool of mature tRNAs into the nuclei causing a decrease in translation efficiency. Mitotically dividing cells appear to be less dependent on translation machinery as they maintain their normal size when deprived of dRNaseZ activity, but rather display a cell cycle arrest at the G2-M transition.